Dinamika Pemanfaatan Lahan Kampung Bersejarah 'Luar Batang' - Jakarta Utara - Popi Puspitasari; Achmad Djunaedi; Bakti Setiawan; Sudaryono S (Forum Teknik, 2011)
The dynamic of land utilization is related to changes of land function. In this contect, the morphological study is impemented to uncover the changes in land functions in Kampung Luar Batang, Nort Jakarta, Indonesia. Kampung Luar Batang is a historical Kampung which was estabished by VOC in Batavia under the influence of existence of a Moslem missionary, Al-Habib Husein bin Abubakar Allaydrus, and accelerated by the its strategic geographical location close to urban economic centers, Historically, Luar Batang has been a place for laborers' settlement, VOC defense port, port of transit for migrants, pilgrimage center and rental dwelling that is surrounded by illegal housing. Each function was not chronologically appeared, but developed in multi-layered manner.In fact the historical meanings of Luar Batang were not obtained through in depth literature study, since the availability of references about the kampung is very limited. This study is an effort to uncover the physical elements of the kampung from historical perspective, based on the maps documentatin and empirical study. The graphical abstraction model presented at this paper is an attempt to clarify the dynamic of land utilization.Keywords : Morphology, Kampung bersejarah, Luar Batang.